(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers critical moments of integration the children with intellectual deviations into the environment of comprehensive school with implementation of inclusive education. The ideas of equality to all the members of society regardless their nationality, gender, race, culture, social position, religion and the individual abilities & capabilities are put in the basis of inclusive education. It is emphasized in the article on the peculiarities of organization of the correction works for the children with intellectual deviations and also there are described the ways of realization the correctional clause in the conditions of general education institution. According to results of the theoretical-methodological analysis that was performed by the authors, it is provided the opinion of the resource teachers about the features of the process of correctional studies & the child guidance for the kids with intellectual deviations. The major point to proceed with effective inclusive education for the children with the intellectual deviations is the development of methods, methodologies actions and principles of special didactics in the educational-integration process. The correction — developing studies foresees the intensified works for the corrections of psychological functions, educational activities, the communicative skills, and the developing of skills, abilities & capabilities for children in the process of manual training